A vibration compensation optimization method for a mobile atomic gravimeter. (17th February 2023) - Gong, Wen-Bin; Li, An; Ma, Jin-Xiu; Tang, Biao; Qin, Fang-Jun
Abstract: Information on the Earth's gravity provides significant strategic support for economies, defense and security. An atomic gravimeter (AG) realizes highly precise measurements of gravitational acceleration by virtue of atomic interference. Vibration noise is a strong contributor to limitations on the measurement sensitivity and accuracy of an AG. Vibration compensation methods thus enhance the environmental adaptability of an AG since it can facilitate the measurement of gravity when an isolation platform is unavailable. A dynamic compensation filter is here devised for correction of the data output from a seismometer, which expands the bandwidth of the seismometer and lowers the distortion of vibration signals. Additionally, a transfer function estimation is introduced to better reflect the actual vibration of the Raman mirror. Based on a simplified transfer function model, this method can modify the interference fringes of the AG in real time. The experimental results show that the proposed optimization method can attenuate the cosine fitting phase uncertainty of interference fringes by up to 85.91%, and reach an uncertainty of about 76.37 μGal in a complicated vibration environment. The AG's measurement accuracy is effectively improved by the proposed method. It is verified that the proposed method is effective and adaptable in a complicated noise environment.